THE AMBIVALENCE OF LIFE IS STRANGE IN PORTRAYING ITS FEMALE CHARACTERS - Oktavanya, Ridanti; Panjaitan, Yasmine Anabel (Sanata Dharma University, 2019)
Nowadays, there has been a new trend in the video game industry to unleash the stereotypical female characters as a response to the increasing criticism toward gender equality in the video game industry. Life is Strange is one example of video games that challenges typical female characters who are usually described as powerless and objectified. However, such a progression has not amended the problematic female representation completely within its narrative. By using the concept of hegemonic masculinity, this paper discusses the ambivalences in Life is Strange in challenging stereotypical female representations. The result of the analysis shows that although Life is Strange successfully subverts the female physical representation through its design, the narrative still perpetuates hegemonic masculinity by means of sacrificial heroine and lesbianism eroticization.DOI:10.24071/ijhs.2019.030102